Diagnóstico de la situación actual de una empresa de servicios de alimentación con respecto al cumplimiento de los requisitos de la norma ISO 9001:2015 para un sistema de gestión de la calidad (2019)
Nowadays, companies around the world are in a highly competitive environment where customers are increasingly demanding and look for products or services whose quality allows them to fully satisfy their requirements; therefore, those who want to remain in the long term must implement strategies that allow them to demonstrate their ability to meet the needs and expectations of their clients and other interested parties. This paper’s purpose is to diagnose the current situation of a food services company regarding the compliance requirements of ISO 9001: 2015 for a quality management system. In order to achieve the objective, the standard requirements were identified initially, then a tool was designed to evaluate the company's compliance of the standard identified requirements, later an audit of the company’s quality management system current situation was carried out in relation with the standard and finally a report of compliance and action plans was presented. The results proved that the company under study has a low compliance concerning the norm.